2020
DOI: 10.3390/su12093782
|View full text |Cite
|
Sign up to set email alerts
|

How Is Climate Change Knowledge Distributed among the Population in Singapore? A Demographic Analysis of Actual Knowledge and Illusory Knowledge

Abstract: Due to the crucial role of knowledge in promoting public engagement with climate change, this study made an in-depths examination of the distribution of climate change knowledge among different demographic groups. Guided by information deficit model and cognitive miser model, two types of knowledge were investigated, including actual knowledge and illusory knowledge. Using a nationally representative survey in Singapore, this study found demographic effects in climate change knowledge distribution. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Poor households have a significantly lower risk perception of climate change's impact on the coastal marine ecosystem (Table 3), which is in line with another study conducted in Singapore which found that low-income households reported a lower level of knowledge compared with higher-income households [99]. Poor households also have significantly lower risk perceptions of the impact of climate change, anthropogenic pressures and marine livelihood on sea grasses and coral reefs compared with not-poor households (Table 5).…”
Section: Incomesupporting
confidence: 86%
See 1 more Smart Citation
“…Poor households have a significantly lower risk perception of climate change's impact on the coastal marine ecosystem (Table 3), which is in line with another study conducted in Singapore which found that low-income households reported a lower level of knowledge compared with higher-income households [99]. Poor households also have significantly lower risk perceptions of the impact of climate change, anthropogenic pressures and marine livelihood on sea grasses and coral reefs compared with not-poor households (Table 5).…”
Section: Incomesupporting
confidence: 86%
“…Poor households also have significantly lower risk perceptions of the impact of climate change, anthropogenic pressures and marine livelihood on sea grasses and coral reefs compared with not-poor households ( Table 5 ). Lower climate change risk perception for poor households compared to not-poor households could be explained by the fact that low-income households and communities develop academic skills at a slower rate than those from higher-income groups [ 99 ]. Poverty levels are strongly linked to educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Poor households have a significantly lower risk perception of climate change's impact on the coastal marine ecosystem, which is in line with another study conducted in Singapore which found that low-income households reported a lower level of knowledge compared with higher-income households [94]. Poor households also have significantly lower risk perceptions of the impact of climate change, anthropogenic pressures, and marine livelihood on sea grasses and coral reefs compared with not-poor households (Table 5).…”
Section: Risk Perceptionssupporting
confidence: 84%
“…Poor households also have significantly lower risk perceptions of the impact of climate change, anthropogenic pressures, and marine livelihood on sea grasses and coral reefs compared with not-poor households (Table 5). Lower climate change risk perception for poor households compared to not-poor households could be explained by the fact that low-income households and communities develop academic skills at a slower rate than those from higher-income groups [94]. Poverty levels are strongly linked to educational attainment.…”
Section: Risk Perceptionsmentioning
confidence: 99%
“…Objective knowledge: One variable consisting of twenty items was included to measure objective knowledge on sustainability [ 67 ]. Each item was a short multiple choice question.…”
Section: Methodsmentioning
confidence: 99%